Photovoltaic devices fabricated from an aqueous dispersion of polyfluorene nanoparticles using an electroplating method - Snaith, H; Friend, R (2004)
We report microscopic and device based analysis of thin films of polyfluorene nanoparticles. We use an electroplating technique to form a complete monolayer of polymer nanoparticles on conductive and polymer-coated substrates. We find the electroplated film to be insoluble in organic solvents, and thus are able to build up multilayer structures of electroactive polymers which are originally soluble in common solvents. By spin-coating an F8BT layer from an organic solvent on top of a PFB:F8BT nanoparticle film, we form a multilayer structure. Capping with an aluminium cathode produces a photovoltaic device with substantial performance characteristics. (C) 2004 Elsevier B.V. All rights reserved.